Struggles and Strategies in Constructing Professional Identity: The First-Year Teaching Experiences of Indonesian EFL Novice Teachers - Aplonia Nelci Ke Lomi; Concilianus Laos Mbato (Universitas Bengkulu, 2020)
Several studies have recorded the increasing number of teachers who left the profession in the first year of teaching in recent years. The main cause is the difficulties over the first year of teaching and the unsatisfactory construction and growth of professional identity. This qualitative study attempted to reveal the struggles faced during their first year of teaching by EFL novice teachers working in Nusa Tenggara Timur, Indonesia and how they coped with those struggles regarding their development of professional identity. The struggles are split into internal and external struggles based on the result. The internal struggles are linked to how teachers controlled their emotions self-efficacy, and ability to teach, their jobs and their personal opinions. The external challenges related to the management of the classroom, the abilities, and attitudes of the students, the lack of resources and facilities in the school, the relationships with their colleagues and their salaries. This research is intended to provide more insight into the realities of teachers working in an underdeveloped province like East Nusa Tenggara, in particular how they establish their professional identity in a lack of facilities and learning resources.Keywords: East Nusa Tenggara; Novice Teachers; Professional Identity; Struggles and Strategies